Effect of Third Party Funding, Financing to Deposit Ratio and Return on Asset for Financing at Bank Muamalat KCP Probolinggo - Millah, Hayatul; Elok Bashiroh (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
The purpose of this research is to determine the influence of third party funds, financing deposit ratio and return on assets on financing in the 2018 period. - 2022 at Bank Muamalat KCP Probolinggo. The type of research used in this study is a quantitative method with a descriptive approach. The sample in this study is the Quarterly financial reports for 2018 to 2022 as many as 20. The data in this study is secondary data. Observation collection method by collecting data on the Annual Financial Report of Bank Muamalat KCP Probolinggo in 2018 - 2022. Banks provide community services and public financial intermediaries. Therefore, banks must always be in the midst of society so that the flow of money from people who have excess can be accommodated and distributed to people who are lacking. One of the bank distribution products is financing provided by one party to another party to support a planned business project, either carried out individually or by an institution. The formulation of the problem in this study is whether there is an influence of third party funds, financing deposit ratio and return on assets on financing for the 2018 to 2022 period. The results of the study show that partially DPK have a significant positive effect and FDR have a Significant negative effect on financing at Bank Muamalat KCP Probolinggo for the 2018-2022 period. Meanwhile, ROA has no significant effect on financing at Bank Muamalat KCP Probolinggo for the 2018-2022 period. Meanwhile, DPK, FDR and ROA simultaneously have a positive effect on financing at Bank Muamalat KCP Probolinggo for the 2018-2022 period. DPK, FDR and ROA contributed 34.1% to financing, the remaining 65.9% was influenced by other variables outside those studied.